Daytime Sleepiness and Quality of Life in Obstructive Sleep Apnoea Patients before and after Long-Term Mandibular Advancement Device Treatment - Signe Halfeld; Liselotte Sonnesen (MDPI AG, 2022)
This study compared daytime sleepiness and quality of life in OSA patients with healthy controls and compared sleepiness and quality of life in OSA patients before and after long-term treatment with a mandibular advancement device (MAD). A total of 27 OSA patients (18 men, 9 women, mean age 52.3 years) and 32 healthy age- and sex-matched controls (20 men, 12 women, mean age 51.1 years) were included. At baseline and after MAD treatment, daytime sleepiness and quality of life were recorded by the Epworth Sleepiness Scale (ESS) and Short Form-36 questionnaires (SF-36). Daytime sleepiness occurred significantly more often in OSA patients compared to controls at baseline (p = 0.01). The quality of life domains Energy and vitality (p < 0.0001), General perception of health (p = 0.0002), Mental health (p = 0.0031), Social functioning (p = 0.0119), Role limitations due to emotional problems (p = 0.0173) and Physical functioning (p = 0.0226) were significantly poorer in OSA patients compared to controls at baseline. After long-term MAD treatment, daytime sleepiness decreased (p < 0.01) and the quality of life domain Energy and Vitality increased (p < 0.01) in OSA patients compared to baseline. The results of the present study support the relevance of MAD treatment as an effective tool for decreasing daytime sleepiness and increasing the quality of life in OSA patients-also in the long term.